2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28214
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Systems and Internet of Things (IoTs) - Challenges in Teaching the ARM Controller in the Classroom

Abstract: several professional articles and five books. One of his books has been translated into Chinese and another one into Greek. His recent book "TinyAVR Microcontroller Projects for the Evil Genius", published by McGraw Hill International consists of more than 30 hands-on projects and has been translated into Chinese and Russian. He is a licensed radio amateur with a call sign VU2NOX and hopes to design and build an amateur radio satellite in the near future. , NSIT pursuing various projects in the field of Embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Undergraduate students in Computer Science (CS), Computer Engineering (CE), and Electrical Engineering (EE) typically have limited hands-on experience with multiple platforms, and rarely any experience with systems. Many current undergraduate IoT courses focus individually on embedded systems [4] [5], hardware [6] [7], or networking [8] , which are important, but possibly miss the educational opportunity of exposing students to the greater breadth of technologies required to deliver an IoT product or service. Similarly, cloud computing courses focus on the cloud infrastructure [9], and less on systems.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Undergraduate students in Computer Science (CS), Computer Engineering (CE), and Electrical Engineering (EE) typically have limited hands-on experience with multiple platforms, and rarely any experience with systems. Many current undergraduate IoT courses focus individually on embedded systems [4] [5], hardware [6] [7], or networking [8] , which are important, but possibly miss the educational opportunity of exposing students to the greater breadth of technologies required to deliver an IoT product or service. Similarly, cloud computing courses focus on the cloud infrastructure [9], and less on systems.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Although the paper delves into details of the framework, it lacks concrete examples of the labware designed for the course. Another example documents the challenges faced in teaching Embedded Systems in the context of IoT, specifically using ARM-based microcontrollers [5]. In conclusion, it was suggested that two different approaches may be used in designing the embedded system course, to simplify teaching: one to include extensive use of Application Programming Interfaces (APIs) provided by manufacturers and the second approach is to teach the course with the systems approach without focusing on hardware, instruction set, and assembly language.…”
Section: Background and Motivationmentioning
confidence: 99%
“…We are building on prior work by others using active learning [6][7][8][9][10][11], PjBL [12][13][14][15][16][17], worked examples [18][19][20], Jupyter notebooks [21,22], agile software development methods [23][24][25], as well as existing IoT course materials [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. However, the existing mechatronics course materials with IoT tend to target Electrical Engineering (EE) and Computer Science (CS) students and the creation of underlying IoT technologies, especially low-level software.…”
Section: Introductionmentioning
confidence: 99%